Selection Against Frameshift Mutations Limits Microsatellite Expansion in Coding DNA - Metzgar, David; Bytof, Jeffrey; Wills, Christopher

(untitled) (Genome Research, 2000)
Microsatellite enrichment is an excess of repetitive sequences characteristic to all studied eukaryotes. It is thought to result from the accumulated effects of replication slippage mutations. Enrichment is commonly measured as the ratio of the observed frequency of microsatellites to the frequency expected to result from random association of nucleotides. We have compared enrichment of specific types of microsatellites in coding sequences with those in noncoding sequences across seven eukaryotic clades. The results reveal consistent differences between coding and noncoding regions, in terms of both the quantity of repetitive DNA and the types present. In noncoding regions, all types of microsatellite (mono-, di-, tri-, tetra-, penta-, and hexanucleotide repeats) are found in excess, and in all cases, these excesses scale in a similar exponential fashion with the length of the microsatellite. This suggests that all types of noncoding repeats are subject to similar mutational and selective processes. Coding repeats, however, appear to be under much stronger and more specific constraints. Tri- and hexanucleotide repeats are found in consistent and significant excess over a wide range of lengths in both coding and noncoding sequences, but other repeat types are much less frequent in coding regions than in noncoding regions. These findings suggest that the differences between coding and noncoding microsatellite frequencies arise from specific selection against frameshift mutations in coding regions resulting from length changes in nontriplet repeats. Furthermore, the excesses of tri- and hexanucleotide coding repeats appear to be controlled primarily by mutation pressure.